Combined pituitary hormone deficiency: current and future status - Castinetti, F.; Reynaud, R.; Quentien, M.-H.; Jullien, N.; Marquant, E.; Rochette, C.; Herman, J.-P.; Saveanu, A.; Barlier, A.; Enjalbert, A.; Brue, T. (Journal of endocrinological investigation, 2015)
Over the last two decades, the understanding of the mechanisms involved in pituitary ontogenesis has largely increased. Since the first description of POU1F1 human mutations responsible for a well-defined phenotype without extra-pituitary malformation, several other genetic defects of transcription factors have been reported with variable degrees of phenotype–genotype correlations. However, to date, despite the identification of an increased number of genetic causes of isolated or multiple pituitary deficiencies, the etiology of most (80–90 %) congenital cases of hypopituitarism remains unsolved. Identifying new etiologies is of importance as a post-natal diagnosis to better diagnose and treat the patients (delayed pituitary deficiencies, differential diagnosis of a pituitary mass on MRI, etc.), and as a prenatal diagnosis to decrease the risk of early death (undiagnosed corticotroph deficiency for instance). The aim of this review is to summarize the main etiologies and phenotypes of combined pituitary hormone deficiencies, associated or not with extra-pituitary anomalies, and to suggest how the identification of such etiologies could be improved in the near future.